'Out of Lust for Money'? Agency and Marital Strategies in Eighth‐Century Italy. (Gender & History, 2022)
This article analyses early medieval Italian marital practices and inquires how Lombard women played the system to increase their agency. It contends that in the eighth century, demographic and social developments created conditions that could favour women in negotiating marriages. These women used their position of power to bargain for better nuptial agreements, resulting in an increase in agency and power within the household. Such perceived imbalance prompted royal authority to intervene, leaving traceable marks in eighth‐century legislation, most notably under King Liutprant (712–44). To contextualise these legal interventions, the article first scrutinises earlier laws for marital practices, introducing basic terms such as morgincap, meta and faderfyo. Then, investigates the demographic and cultural factors related to marriages, including the distribution of the population, the level of celibacy and monastic confinement and rules that limited marital arrangements (such as legislation against incest). Finally, it considers Liutprant's laws for evidence of strategies used by women, considering the dialectics between agency and normative constraints.